2020
DOI: 10.1186/s12871-019-0928-y
|View full text |Cite
|
Sign up to set email alerts
|

Adding dexmedetomidine to morphine-based analgesia reduces early postoperative nausea in patients undergoing gynecological laparoscopic surgery: a randomized controlled trial

Abstract: Background: Few studies have investigated the effect of dexmedetomidine on postoperative nausea and vomiting (PONV) in patients underwent gynecological laparoscopic surgery. We investigated if adding dexmedetomidine to a morphine-based patient-controlled analgesia (PCA) could decrease the incidence of PONV in this high-risk patient population. Methods: In this prospective, randomized, double-blind and placebo-controlled study, 122 patients underwent gynecological laparoscopic surgery were assigned into two gro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Finally, the patients were limited to those undergoing gynecological pelviscopic surgery, and the number of participants was relatively small. However, female patients, pelviscopic surgery, and intraoperative opioid use may increase the incidence of PONV [ 26 , 27 ]. The strength of this study is that it was conducted in patients expected to have a high incidence of PONV.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the patients were limited to those undergoing gynecological pelviscopic surgery, and the number of participants was relatively small. However, female patients, pelviscopic surgery, and intraoperative opioid use may increase the incidence of PONV [ 26 , 27 ]. The strength of this study is that it was conducted in patients expected to have a high incidence of PONV.…”
Section: Discussionmentioning
confidence: 99%
“…Although some prospective studies with small sample sizes have shown that a 0.5 or 1.0 μg/kg bolus infusion could effectively decrease the incidence of PONV ( 7 9 , 15 , 16 ), there have been few studies on other doses, and it is not clear whether there was a dose-dependent antiemetic effect. The optimal dose of DEX for achieving antiemetic effects has not been well-documented.…”
Section: Discussionmentioning
confidence: 99%
“…Geng ZY et al demonstrated that dexmedetomidine administration had lower incidence of nausea, which attributed to sympatholytic and opioid-sparing effect of dexmedetomidine [ 24 ]. The results from Li HJ et al showed that dexmedetomidine reduced the incidence of nausea not vomiting at 2 h after operation [ 25 ]. In our study, we observed that dexmedetomidine administration significantly decreased remifentanil requirement, postoperative pain VAS scores, and consumption of fentanyl.…”
Section: Discussionmentioning
confidence: 99%